Transformation of Production Organization of Dusung based Nutmeg Plantation (Case Study of Industrial and Farmers' Partnership in Hila Village, Moluccas Province) - Siwalette, Jeter Donald (Advances in Social Sciences Research Journal, 2018)
This paper provides new information that is rarely studied, related to the organization transformation of dusung based nutmeg plantation production. This research is aimed to know the transformation of production organization of nutmeg plantation based on dusung because partnership between community of nutmeg farmer and plantation industry in Hila village. The method used is qualitative research, using case study strategy. The sample was determined by purposive sampling with snowball technique. To obtain detailed data, informants and key informants are interviewed, ranging from village heads, community leaders, and village government staff, who knew the dusung. Furthermore, key informants who knew the plantation industry are company leaders, production managers, general managers, employees as informants who know the presence of industry and farmers who collaborate with the industry. Secondary data is obtained from documents of research results and industry progress reports. The result of the research shows that the presence of industry causes transformation of production organization, land resource management, technology and technique of nutmeg cultivation, production relation and orientation of nutmeg farmer based on dusung to organization of industrial production. This study is expected to contribute to other researchers who examine the typical agricultural production organization in a region due to the infiltration of the plantation industry. It also provide information that by the entry of industry in a region, the culture of local communities that become the primary source of income society is expected not to be reduced.